NORTH CAROLINA FAMILY AND CONSUMER SCIENCES STUDENTS : HOW STUDENTS PERCEIVE THE VALUE OF THEIR CLASSES CURRENTLY AND FOR THEIR FUTURES - Lambeth, Jennifer C. (East Carolina University, 2015)
Family and Consumer Sciences (FCS) secondary courses offer students opportunities to explore career pathways, and gain invaluable self-sufficiency life skills such as how to prepare healthy and nutritious meals, how to solve problems, how to parent children, and how to manage personal, family, and financial d resources. FCS courses also integrate core academic skills and work place soft skills. Although these courses are popular in Career and Technical Education, and it is commonly believed that students value the concepts and skills learned through them, impact data on the benefits of these courses from the student's perspective is lacking in the literature. The research objectives for this study included examining the demographic characteristics of students from three high schools in North Carolina who completed an online survey (n = 378),their perceptions of the value of their FCS courses currently and for their future career and life plans. Descriptive statistics, using frequency and percentages and cross-tabs, allowed an expanded data analysis across variables. The findings revealed that high school students wanted to take FCS courses; they enjoy their FCS courses, and value them currently and believe all students should take these courses; students see the value of taking FCS courses for their future career and life plans; and believe their FCS classes are beneficial. Recommendations include completing analysis of accompanying qualitative open-ended responses, conduct more studies that cover a larger geographical area, and include measurement of specific soft skills to gather more concrete impact data for Family and Consumer Sciences.
Keywords: Education; Individual and family studies; Secondary education; Career and technical education; Family and consumer sciences; Family preparation; Life and career preparation; Obesity; Home economics students--Attitudes--Research--North Carolina; High school students--Vocational guidance--North Carolina